Assessing the Hardness of Quenched Medium Steel Using an Ultrasonic Nondestructive Method - Shao-Yi Hsia; Yu-Tuan Chou (Advances in Materials Science and Engineering)
Developing new materials or improving their heat treatment techniques is key to industrial upgrades for increasing fastener product quality. Nowadays, high tensile strength bolts are heat-treated to achieve desired mechanical properties such as hardness, strength, toughness, and resistance to fatigue and wear. Ultrasound detection is one widely used nondestructive inspection technique. Based on the characteristics of wave transmission, the refraction, diffraction, and scattering of ultrasound wave velocity and attenuation in a material are governed by its grain boundary characteristics. In this study, C1045 middle carbon steel was heat-treated at various temperatures and then water-quenched, and the relationships among grain size, ultrasonic velocity, attenuation, and material hardness were then determined using two ultrasound sources. Our experimental results show that a smaller average grain size as well as higher hardness can be obtained from higher quenching temperatures. Faster acoustic velocities and slower attenuation coefficients are caused by higher material hardness. A scattering effect is more obvious for higher transducer frequencies. Our results demonstrate another nondestructive test that can assess the quenching process in the fastener industry.